Modern information technologies in the hotel business: development trends and implementation issues - Voronova Olga; Khareva Viktoria; Khnykina Tatyana (E3S Web of Conferences, 2020)
This article discusses the main developments in information technologies of the hotel business, which is especially relevant due to the fact that today the process of economy digitalization in the Russian Federation significantly influences hospitality industry. Automation of hotels associated with the use of modern technologies particularly improves the quality of customer service. In this research major trends in the development of information technologies in hotel business were identified. They include: cloud computing, artificial intelligence, blockchain, augmented reality, etc. This paper defines the main problems of introduction of modern information technologies in hospitality industry. The study revealed that currently, information technologies are improving rapidly, directly impacting hotel business, but also assessing hotel market of the Russian Federation. In terms of development and use of modern information technologies it is important to note that a lot depends on management of a specific hospitality enterprise.